Sovereign Acts : Contesting Colonialism Across Indigenous Nations and Latinx America. - Negrōn-Muntaner, Frances (University of Arizona Press, 2017)
This paradigm-shifting work examines the new ways colonized peoples resist subjugation and reclaim rights and political power--Provided by publisher.